2017
DOI: 10.1007/s11845-017-1694-9
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in postoperative cataract care: impact of electronic patient records in optometrist-delivered shared care

Abstract: Optometrists provided an excellent postoperative care service with superior postoperative feedback rates compared to hospital doctors. EPRs facilitate a postoperative shared-care pathway that is of high quality and efficiency with major economic advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A possible reason for the low hire of optometrists is the administrative preference for eye care delivery models involving ophthalmic assistants for the provision of screening, history taking, refraction, and investigative procedures and ophthalmologists for the provision of medical and surgical care. This model, although economically advantageous for the targeted large volume of patient care, has the potential to significantly compromise patient care, and contrasts with the successful eye care delivery models around the world that have demonstrated the efficient role of optometrists in areas such as pre-operative and post-operative care for cataracts, glaucoma management, review of patients with diabetes, and pediatric eye care 86–88 . In countries such as Australia and the United Kingdom, optometry practice extends into the comanagement of cataracts, glaucoma, and diabetic retinopathy 89–91 .…”
Section: Present and Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for the low hire of optometrists is the administrative preference for eye care delivery models involving ophthalmic assistants for the provision of screening, history taking, refraction, and investigative procedures and ophthalmologists for the provision of medical and surgical care. This model, although economically advantageous for the targeted large volume of patient care, has the potential to significantly compromise patient care, and contrasts with the successful eye care delivery models around the world that have demonstrated the efficient role of optometrists in areas such as pre-operative and post-operative care for cataracts, glaucoma management, review of patients with diabetes, and pediatric eye care 86–88 . In countries such as Australia and the United Kingdom, optometry practice extends into the comanagement of cataracts, glaucoma, and diabetic retinopathy 89–91 .…”
Section: Present and Future Challengesmentioning
confidence: 99%
“…This model, although economically advantageous for the targeted large volume of patient care, has the potential to significantly compromise patient care, and contrasts with the successful eye care delivery models around the world that have demonstrated the efficient role of optometrists in areas such as pre-operative and post-operative care for cataracts, glaucoma management, review of patients with diabetes, and pediatric eye care. [86][87][88] In countries such as Australia and the United Kingdom, optometry practice extends into the comanagement of cataracts, glaucoma, and diabetic retinopathy. [89][90][91] Nepalese optometrists currently provide some aspects of these enhanced eye care services (e.g., pre-surgical and post-surgical care, glaucoma monitoring, and emergency triage) in both hospital and private practice settings, but no established model or pathway that formally streamlines such collaborative care approach is in practice.…”
Section: Present and Future Challenges Clinical And Regulatory Challe...mentioning
confidence: 99%
“…Shared care with community optometrists has been shown to be highly effective in cataract care pathways [7,8]. A previous study carried out by our group showed that community optometrists provide superior post-operative feedback compared to doctors [9]. High sensitivity and specificity for recognition of post-operative complications has been demonstrated in co-managing optometrists [10].…”
Section: Introductionmentioning
confidence: 99%